Analysis of quantitative investment strategies - unraveling the Esg low-volatility link: do Esg provide risk-adjusted returns in European markets - Calafate, Ana Teresa de Sousa (2023)
This paper addresses the gap in understanding the link between ESG criteria and the low volatility signal in the European Market. Best-in-class and worst-in-class portfolios, based on ESG scores and volatility individually and subsequently on a combined strategy, consistently show that low ESG score decile stocks outperform top decile stocks in both individual and combined strategies. Both portfolios provide positive significant alphas against CAPM and FF5, with the lower ESG portfolio demonstrating superior alphas. However, conflicting results are found in the group part of the field lab, proving distinct outcomes between the United States and European markets.